Quantitative interpretation of seismic attributes for reservoir characterization of Early-Middle Miocene syn- and post-rift successions (Songkhla Basin, Gulf of Thailand) - Jidapa Phoosongsee (2019)
© 2019 The major hydrocarbon reservoirs in the Gulf of Thailand, including the Songkhla Basin, are deposited throughout the syn- and post-rift section (Late Eocene-Recent), with the main reservoirs occurring in the Early Miocene to Middle Miocene section. These reservoirs are predominantly fluvial channels with complex lateral and vertical geometries and distributions particularly as point bars, overbank deposits, and sand- or mud-filled channels. This study characterizes the reservoir architecture and depositional environment of Songkhla Basin from late syn-rift to post-rift, during the Miocene, by integrating the seismic attributes (RMS, similarity, and spectral decomposition), well log interpretations, and well biostratigraphic data. Two distinctive channel characteristics and patterns were interpreted: (A) N-S oriented meandering channel complexes, aligned sub-parallel to the western boundary faults, developed during the late syn-rift (upper Early Miocene), (B) NE-SW oriented long, narrow fluvial channels with tidal and marine influence, developed in the post-rift phase I (Middle Miocene). These channel orientations reflect changes in the basin architecture passing from the late syn-rift stage to the post rift. Syn-rift channel orientation was controlled by topography created by motion on the western boundary fault system, while during the post-rift stage channel orientations were affected by mild inversion on the boundary fault system and thermal subsidence, which resulted in an eastward shift in the basin depocentre towards the flexural margin.